Chloride Ion Corrosion Pattern and Mathematical Model for C60 High-Strength Concrete after Freeze-Thawing Cycles. (8th April 2021) - Li, Yan; Li, Bing; Zhang, Lian-ying; Ma, Chao; Zhu, Jiong; Li, Ming; Pu, Hai
Abstract : In this study, the porosities of C60 high-strength concrete after 0, 30, 60, and 90 freeze-thaw cycles determined via the water retention method are 1.30%, 3.65%, 5.14%, and 7.34%, respectively. Furthermore, a mathematical model of porosity varying with the number of freeze-thaw cycles is established. Using an artificial environment simulation experimental system and the natural diffusion method, the chloride diffusion law of C60 high-strength concrete after 0, 30, 60, and 90 freeze-thaw cycles is obtained. The corresponding diffusion coefficients are calculated based on the experimental results and Fick's law, where 0.3431 × 10 −12, 0.5288 × 10 −12, and 0.6712 × 10 −12, and 0.8930 × 10 −12 m 2 /s are obtained, respectively, and a mathematical model of diffusion coefficient with freeze-thawing is established. Transport control equations comprising solution flow and solute migration control equations are established for chloride ions in concrete after freeze-thawing cycles. The equations consider the effects of freeze-thawing, solution pressure, solution concentration, solution density, convection, mechanical dispersion, and chemisorption on chloride ion transport in concrete. Using COMSOL numerical software, the transport control equations for chloride ions are solved using a real concrete numerical model, and the chloride ion corrosion process in concrete after freeze-thaw cycles is simulated. The simulation results are consistent with the experimental values.